Performance Analysis of Support System Personnel at the Secretariat General of the House of Representatives of the Republic of Indonesia - Rosweni Sukandar; Ridwan Rajab; Hamka Hamka (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to identify the factors that cause the suboptimal performance of SSP at the Secretariat General of the House Of Representatives Of The Republic Of Indonesia so that it can provide a better understanding in improving SSP performance to support the achievement of the vision, mission and objectives of the Secretariat General of the House Of Representatives Of The Republic Of Indonesia and to determine the right strategy in optimizing SSP performance at the Secretariat General of the House Of Representatives Of The Republic Of Indonesia. This research method uses a qualitative approach that produces descriptive data. The results showed that the less than optimal performance of SSP in the Secretariat General of the House of Representatives was caused by factors of competence, motivation, and organizational support. Support from the Secretariat General of the House Of Representatives Of The Republic Of Indonesia in developing SSP will provide significant benefits both for the organization of the Secretariat General of the House Of Representatives Of The Republic Of Indonesia and for SSP itself. For the House Of Representatives Of The Republic Of Indonesia Secretariat General, the development of SSP will increase productivity and performance. Meanwhile, for the SSPs, this will increase their competence in carrying out tasks and solving work problems. This support also motivates SSPs to continue learning and developing new knowledge, skills, and work behaviors that support task execution. Thus, SSPs will better understand their duties and responsibilities and have opportunities to develop themselves. Therefore, SSP competency development can be an important strategy for the House Of Representatives Of The Republic Of Indonesia Secretariat General to optimize individual and organizational performance.